2017
DOI: 10.1021/acs.jafc.7b04067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 60-Week Feeding Diet Containing Bt Rice Expressing the Cry1Ab Protein on the Offspring of Inbred Wuzhishan Pigs Fed the Same Diet

Abstract: We evaluated the chronic effects of Bt rice carrying the Cry1Ab protein (1.64 mg/kg) on offspring of highly inbred WZSP, fed with Bt rice for 360 days, in a 60-week feeding study. The WZSP offspring (n = 27) were assigned to two groups (Minghui86 group, female n = 6, male n = 5; Bt group, female n = 11, male n = 5). The average obtained Cry1Ab protein dosage for female and male pigs was 1.003 and 1.234 mg/kg body weight after 10 weeks of feeding, respectively. The experimental feed in the study was nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Many kinds of research were conducted to evaluate the safety of GM feeding in pigs and rabbits either by giving Bt rice (Liu et al, 2018a, Liu et al, 2018b, Liu et al, 2017 or Bt maize (Chen et al, 2016, Yalçin et al, 2018 presented in Table 2. Chen et al, (2016) conducted a study to investigate the chronic effect of transgenic maize comprise of Cry1Ab protein (1.64 mg/kg) to evaluate the growth performance, immune response and health of Wuzhishan pig after 196-day GM maize feeding.…”
Section: Effects Of Feeding With Gm Crops On Pigs and Rabbitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many kinds of research were conducted to evaluate the safety of GM feeding in pigs and rabbits either by giving Bt rice (Liu et al, 2018a, Liu et al, 2018b, Liu et al, 2017 or Bt maize (Chen et al, 2016, Yalçin et al, 2018 presented in Table 2. Chen et al, (2016) conducted a study to investigate the chronic effect of transgenic maize comprise of Cry1Ab protein (1.64 mg/kg) to evaluate the growth performance, immune response and health of Wuzhishan pig after 196-day GM maize feeding.…”
Section: Effects Of Feeding With Gm Crops On Pigs and Rabbitsmentioning
confidence: 99%
“…Longterm feeding Bt corn results had no adverse effects of GM maize on pigs. Later on, Liu et al, (2017) performed an experiment to evaluate the chronic effects of Bt rice carrying the Cry1Ab protein (1.64 mg/kg) on offspring of highly inbred Wuzhishan pigs. The result showed that only difference occurs in the average daily gain and feed conversion ratio (FCR) of the females in week 3 and males from weeks 1 to 10 were different between both groups and the body weight of the male pigs in week 2 was greater in the non-GM group than that of the Bt group (P<0.05).…”
Section: Effects Of Feeding With Gm Crops On Pigs and Rabbitsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, transgenic Bt rice is safer to aquatic ecosystems than its non-transgenic counterpart. The abundance and diversity of zooplankton were significantly higher in Bt rice fields than non- Bt rice fields, because Bt rice required reduced pesticide application therefore produced lower pesticide residues in the field water body 25,26 . Finally, safety of Bt -transgenic rice to the vertebrates were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, safety of Bt -transgenic rice to the vertebrates were investigated. Impact of Bt transgenic rice on frogs 27,28 , rats 2932 , pigs 26 , and macaques 33 was intensively studied. Through a 90-days feeding assay, no differences were observed between the rats feeding on genetically modified rice and non-genetically modified rice in term of a range of parameters, including microflora composition, intestinal permeability, epithelial structure, fecal enzymes, bacterial activity, and intestinal immunity 34 .…”
Section: Introductionmentioning
confidence: 99%